Comparing Methods for Identifying Bacillus Strains Capable of Producing the Antifungal Lipopeptide Iturin A - Hsieh, Feng-Chia; Lin, Tsung-Chun; Meng, Menghsiao; Kao, Suey-Sheng (Current microbiology, 2008)
Lipopeptides represent a unique class of bioactive microbial secondary metabolites, and iturin A shows attractive antibiotic properties among them. This study compares three methods, such as yeast/fungal growth inhibition assay, quantitative high-performance liquid chromatography (HPLC) and polymerase chain reaction (PCR) for identifying a number of Bacillus species that produce iturin A. We examined the feasibility of screening iturin A-producing Bacillus strains by PCR using specific primers for ituD and lpa-14 amplification. Twenty standard strains and 120 field-collected Bacillus spp. isolates were tested in this study. Four B. subtilis and one B. circulan strains from ATCC, and B. amyloliquefaciens B128, a known iturin A producer, exhibited positive results. Of the 120 field-collected isolates, 42 strains were positive. The potential of producing iturin A by these PCR-positive strains were then confirmed by conventional methods such as fungal growth inhibition assay and HPLC analysis. The consistency between results of PCR, HPLC, and fungal growth inhibition assay suggests that the PCR method could be used as an alternative tool for fast screening of iturin A-producing Bacillus strains from the environment. This is the first report of detecting iturin A production from B. circulans.